2022
DOI: 10.1002/ppul.26164
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of maternal depression and early childhood asthma and wheeze: Effect modification by child sex

Abstract: Background: Studies report associations between maternal mental health and adverse respiratory outcomes in children; however, the impact of timing and duration of maternal distress remains understudied. We sought to longitudinally examine associations between maternal depression and childhood asthma and wheeze, and explore sex differences. Methods: Maternal depression (n = 601) was assessed using the Edinburgh Depression Scale questionnaire, dichotomized at a clinically relevant cutoff (>12) (a) during pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…A longitudinal study in Mexico, examining 601 pairs of mothers and infants, in order to comprehend the correlation between maternal depressive symptoms and childhood asthma. The study found that maternal postpartum depression or recurrent depression was highly associated with asthma in children at 48 months ( 66 ). A large data survey in Korea found that maternal depression was significantly associated with childhood asthma (OR = 2.03) and AD (OR = 1.76) ( 69 ).…”
Section: Common Risk Factors For Allergy and Tdmentioning
confidence: 99%
“…A longitudinal study in Mexico, examining 601 pairs of mothers and infants, in order to comprehend the correlation between maternal depressive symptoms and childhood asthma. The study found that maternal postpartum depression or recurrent depression was highly associated with asthma in children at 48 months ( 66 ). A large data survey in Korea found that maternal depression was significantly associated with childhood asthma (OR = 2.03) and AD (OR = 1.76) ( 69 ).…”
Section: Common Risk Factors For Allergy and Tdmentioning
confidence: 99%
“…10 Most studies on parental depression and childhood asthma have focused on the mothers of the affected children. 11,12 Treatment of maternal depression leads to improved asthma management and reduced asthma costs. 13 Fathers of children with asthma usually comprise less than 10% of the caregiver sample in studies that investigated caregiver mental illness, 14 and the effect of paternal depression management on offspring asthma control is not known.…”
Section: Introductionmentioning
confidence: 99%